2008
DOI: 10.1063/1.2842065
|View full text |Cite
|
Sign up to set email alerts
|

Stretching an anisotropic DNA

Abstract: We present a perturbation theory to find the response of an anisotropic DNA to the external tension. It is shown that the anisotropy has a nonzero but small contribution to the force-extension curve of the DNA. Thus an anisotropic DNA behaves like an isotropic one with an effective bending constant equal to the harmonic average of its soft and hard bending constants.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…In [84], Eslami-Moossallam and Ejtehadi have introduced the following effective Hamiltonian for the description of the dynamics of an anisotropic DNA molecule. (397) is non-Hermitian, but it is at the same time real, i.e., it commutes with the time-reversal operator T .…”
Section: Biophysicsmentioning
confidence: 99%
“…In [84], Eslami-Moossallam and Ejtehadi have introduced the following effective Hamiltonian for the description of the dynamics of an anisotropic DNA molecule. (397) is non-Hermitian, but it is at the same time real, i.e., it commutes with the time-reversal operator T .…”
Section: Biophysicsmentioning
confidence: 99%
“…κ 1 , κ 2 , and ω) respectively correspond to rotation of the filament aroundd 1 , d 2 , andd 3 and called tilt, roll and twist [21]. Therefore, the elastic energy of an inextensible, unshearable and anisotropic filament in harmonic approximation can be written as [54,60] …”
Section: Fig 2: Parametrization Of the Elastic Rodmentioning
confidence: 99%
“…The sequencedependent bending anisotropy of B-DNA has been observed in X-ray crystallography of DNA-protein complexes [40,41] and NMR spectroscopy [42], as well as allatomistic simulations [43][44][45][46][47][48][49][50]. Many theoretical studies have considered such anisotropic bending into the elastic models [51][52][53][54][55][56], and it is shown that although the bending anisotropy affect the elastic properties of a short DNA molecule in 3D, it becomes unimportant when the DNA segment is long enough to include a few full helical turns [54,57].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations